PENGARUH STRUKTUR KEPEMILIKAN INSTITUSIONAL, FINANCIAL DISTRESS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP KONSERVATISME AKUNTANSI - Novia Hari Wulandari, 11.05.52.0130; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2015)
The study examines the effect of institutional ownership structure, financial distress, leverage and firm size on conservatism accounting. This research was conducted at the Indonesian Stock Exchange by using a go public manufacturing company as the unit of analysis. The sampling method used purposive sampling with the observation period from 2010 to 2013. Relatonship and (or) influence between variable is described by using multiple regression analysis. The result showed that the institutional ownership structure and financial distress had no effect to the conservatism accounting. While, the leverage and the firm size has positive effect and significant to the conservatism accounting.Keywords: Conservatism Accounting, Institutional Ownership Structure, Financial Distress, Leverage and Firm Size